The Safety Profiles of Adalimumab, Infliximab, Etanercept, Secukinumab and Ustekinumab in Psoriasis - A 30-month Observational Cohort Prospective Study of Adverse Events in Biologic Therapy - Paluch, Zoltán; Marques, Emanuel; Boháč, Petr; Zemková, Kateřina; Hercogová, Jana (Acta dermatovenerologica Croatica, 2024)
BACKGROUND: Although biologic agents are very effective, long-term comparative studies demonstrating their safety relative to one another are still lacking. METHODS: A total of 124 patients with psoriasis were followed up for 30 months; 74 received anti-TNF-alpha inhibitors (adalimumab, etanercept, infliximab), 33 were on ustekinumab, and 17 were treated with secukinumab. The rates of adverse events in these groups were recorded and statistically analyzed. RESULTS: Infliximab-treated patients showed a high occurrence of asymptomatic, but increased liver enzymes, fatigue, and respiratory as well as dermatologic infections. Adalimumab-treated patients were more often affected by musculoskeletal disorders and infections of all types. Patients treated with secukinumab presented with higher rates of cardiovascular disorders as well as respiratory and dermatologic infections. The group receiving etanercept was more often diagnosed with musculoskeletal and reproductive disorders, specifically menstrual disorders. The rates of therapy discontinuation and serious adverse events did not reach statistically significant values. CONCLUSION: A higher incidence of adverse events was observed among adalimumab-, and infliximab-treated patients, with ustekinumab found to have the safest profile. Our results demonstrate that a personalized approach, including evaluation of a patient's risk profile, is necessary before commencing a biologic. Further research is warranted to confirm the findings of our study.
Keywords: Infliximab; Humans; Etanercept; lidé středního věku; Psoriasis; kohortové studie; infliximab; Female; Antibodies, Monoclonal; dermatologické látky; dospělí; psoriáza; etanercept; lidé; humanizované monoklonální protilátky; Adalimumab; Cohort Studies; Adult; Antibodies, Monoclonal, Humanized; ženské pohlaví; Male; Middle Aged; Ustekinumab; ustekinumab; monoklonální protilátky; Dermatologic Agents; mužské pohlaví; prospektivní studie; adalimumab; Prospective Studies